Karakteristik Histori Bencana Indonesia Periode 1815 – 2019 Berdasarkan Jumlah Bencana, Kematian, Keterpaparan dan Kerusakan Rumah Akibat Bencana - Jihan Fitriyani; Rio Khoirudin Apriyadi; Tri Winugroho; Dedy Hartono; I Dewa Ketut Kerta Widana; Wilopo Wilopo (PendIPA Journal of Science Education, 2021)
[Historical Characteristics of Disasters in Indonesia for the Period 1815 - 2019 Based on the Number of Disasters, Deaths, Exposure and Damage to Houses Due to Disasters] Indonesia is a country with high potential for disasters in the world. Natural, non-natural and social disasters in Indonesia must be able to be used as laboratories and disaster experts as a form of state protection for its people. This paper aims to describe the historical characteristics of disasters based on indicators of the number of disaster events, deaths, exposure, and damage to houses due to disasters. We found that the characteristics differed in each of the indicators studied. Meanwhile, the increasing graph is shown by each indicator in this study. Analysis of the historical characteristics of disasters is an important tool needed to support sustainable disaster management programs.